A note on the origins of The General Theory of Second Best: The accounts of Kelvin John Lancaster, Richard George Lipsey and Harry Gordon Johnson - Julien Gradoz (Duke University, Center for the History of Political Economy (CHOPE), 2025)
In welfare economics, the theory of second best is inextricably linked to an article by Richard George Lipsey and Kelvin John Lancaster, published in 1956 in the Review of Economic Studies. The publication of this article was encouraged by Harry Gordon Johnson, who was a member of the journal's editorial board at the time. Over the years, these three economists have reflected on the origins of this article. While their accounts share common elements, they also diverge significantly, particularly regarding the allocation of scientific credit. This note seeks to compare their accounts, to provide context about the intellectual environment surrounding the article's conception and to highlight the relationships between these three economists.
Keywords: B21; D04; 330; Second Best; Kelvin John Lancaster; Richard George Lipsey; Harry Gordon Johnson